Fundraising Strategies for Dompet Ummat Institute of Pontianak City - suraji suraji; Santa Rusmalita (J-MD Jurnal Manajemen Dakwah, 2020)
The Dompet Umat Institution is a non-profit organization, researchers asking for help to find out more about raising funds conducted by the social organization Dompet Ummat in Pontianak. Therefore, researchers want to discuss more deeply about how the strategy of the Dompet Ummat Institute in raising funds in the city of Pontianak. With the formulation of the problem (1) What is the fundraising strategy of the Dompet Ummat Institution in looking at opportunities in the field? (2) How does the Dompet Ummat Institute in Formulating fundraising strategies for proposing existing benefits? (3) How does the Dompetku Institution implement the fundraising strategy? (4) How does the Dompet Ummat Institute conduct monitoring and evaluation after conducting a fundraising strategy? In conducting this research the writer will use a descriptive method, which this study will discuss, describe and describe the investment strategy of fundraising for the Dompet Ummat Institution. It can be concluded that (1) the Dompet Institute looks at the opportunities that exist in the field by using various media tools both from online and online media that support to search for any type of opportunity in the field. (2) The Dompet Institute in formulating fundraising strategies by making programs and then designing from the program as interesting as possible can awaken potential donors. (3) Dompet Ummat Institution in implementing the fundraising strategy by providing donation shuttle services. The Dompet Ummat Institution in monitoring and evaluating ongoing programs follows these programs, those who participate in controlling all parties of the Fundraising team itself. Keywords: Fundraising Strategies, Zakat Management, Dompet Ummat Institute of Pontianak City